High‐Performance Flexible Transparent Electrode with an Embedded Metal Mesh Fabricated by Cost‐Effective Solution Process. Issue 22 (29th March 2016) - Khan, Arshad; Lee, Sangeon; Jang, Taehee; Xiong, Ze; Zhang, Cuiping; Tang, Jinyao; Guo, L. Jay; Li, Wen‐Di
Abstract : A new structure of flexible transparent electrodes is reported, featuring a metal mesh fully embedded and mechanically anchored in a flexible substrate, and a cost‐effective solution‐based fabrication strategy for this new transparent electrode. The embedded nature of the metal‐mesh electrodes provides a series of advantages, including surface smoothness that is crucial for device fabrication, mechanical stability under high bending stress, strong adhesion to the substrate with excellent flexibility, and favorable resistance against moisture, oxygen, and chemicals. The novel fabrication process replaces vacuum‐based metal deposition with an electrodeposition process and is potentially suitable for high‐throughput, large‐volume, and low‐cost production. In particular, this strategy enables fabrication of a high‐aspect‐ratio (thickness to linewidth) metal mesh, substantially improving conductivity without considerably sacrificing transparency. Various prototype flexible transparent electrodes are demonstrated with transmittance higher than 90% and sheet resistance below 1 ohm sq −1, as well as extremely high figures of merit up to 1.5 × 10 4, which are among the highest reported values in recent studies. Finally using our embedded metal‐mesh electrode, a flexible transparent thin‐film heater is demonstrated with a low power density requirement, rapid response time, and a low operating voltage. Abstract : Vacuum‐free solution‐processed fabrication of flexible embedded metal‐mesh transparent electrodes is demonstrated. The fabrication features a combination of lithography, electrodeposition, and imprint transfer, which is scalable for large‐area high‐throughput production with sub‐micrometer linewidth. A self‐anchoring structure of thick metal mesh contributes to excellent stability and a high electrical to optical conductivity ratio of up to 1.5 × 10 4 .